Preparation method of low-temperature glass lining porcelain glaze

By introducing specific components and processes, high viscosity and water resistance porcelain glaze was prepared, which solved the problems of high firing temperature and easy coating falling off in the existing glass-lined porcelain glaze, and achieved the preparation of low-temperature sintering and high wear resistance coating.

CN119683857AInactive Publication Date: 2025-03-25SHANDONG HUAXING SPECIAL EQUIP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510222319.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing glass-lined porcelain glaze preparation process has a high firing temperature and the coating is prone to fall off, making it difficult to meet the needs of low-temperature sintering and high wear resistance.

Method used

By introducing components such as frit, clay and silica, low-temperature ball milling and batch ball milling processes, combined with low-temperature sintering technology, a high viscosity and water-resistant ceramic glaze is prepared, and a dense and firm bonding coating is formed by enamel coating.

Benefits of technology

The glass-lined porcelain glaze coating with low temperature sintering is achieved, which improves its wear resistance, corrosion resistance and heat resistance, avoids the problem of coating falling off, and enhances its resistance to acid and alkali corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of glass lining preparation, in particular to a preparation method of low-temperature glass lining porcelain glaze, which comprises the following steps: step a, weighing required raw materials according to components, putting the raw materials into a ball mill, and intermittently ball-milling; b, heating the ball-milled raw materials to 700 DEG C, and removing moisture and impurities; c, the temperature continues to be increased to 1200 DEG C for 0.5-1 h, and the temperature is made to be in a molten state; d, pouring the molten ceramic glaze in the step c into water, filtering, and drying the crushed particles to remove moisture; and e, after the ceramic glaze is prepared, the surface of a metal matrix is coated with the ceramic glaze through an enamel coating method, and a compact and firmly-combined coating is formed through calcination. According to the invention, silicon dioxide is introduced through the frit and the clay, and a proper ratio is obtained through discussion, so that the viscosity of the porcelain glaze is improved, the fluidity of the glaze during melting is reduced, the resistance of the porcelain glaze to water solubility and chemical erosion is improved, and a coating formed by low-temperature sintering is stable and is not easy to fall off in a use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass enamel preparation, and in particular to a method for preparing low-temperature glass enamel. Background Art

[0002] Enamel is a composite material composed of a metal matrix and an inorganic porcelain layer, and its performance is significantly better than that of a single metal or inorganic material. Enamel has good corrosion resistance, high temperature resistance and easy cleaning properties, and is widely used in industries such as construction, petrochemicals, medicine, and traditional daily necessities. The raw materials of enamel are mainly divided into base agents, solvents, adhesion agents, and colorants.

[0003] The quality of the substrate used for enamel directly affects the performance of enamel products. Currently, the commonly used enamel substrates are steel, cast iron, aluminum and its alloys, and titanium alloys, among which the vast majority are based on steel. Common impurity elements in these substrates include carbon, silicon, manganese, phosphorus, sulfur, chromium, and nickel. The carbon element affects the mechanical processing properties of the substrate. Adding an appropriate amount of carbon can improve the plasticity and enamelability of the substrate, but too high a content will affect the forming of the metal substrate. The role of silicon is to adjust the thermal expansion coefficient of the substrate and improve the compatibility of the substrate and the porcelain layer. Enamel coating is an inorganic coating that is very suitable for the surface protection of weather-resistant steel. The general firing temperature is above 800°C. Not only is the firing temperature high, but conventional enamel coatings may fall off after long-term use. Therefore, the preparation process of enamel is still a problem worth exploring. Summary of the invention

[0004] In view of the problems existing in the background technology, the present invention improves the existing preparation process of glass-lined enamel and provides a preparation method of low-temperature glass-lined enamel.

[0005] The method for preparing low-temperature glass enamel comprises the following steps: Step a: Weigh the required raw materials according to the components, put them into a ball mill, and perform intermittent ball milling; Step b: heating the ball-milled raw material to 700°C to remove moisture and impurities; Step c: Continue heating to 1200°C for 0.5 to 1 hour to make it molten; Step d: then pouring the molten enamel in step c into water, filtering, and drying the crushed particles to remove moisture; Step e: After the enamel is prepared, it is coated on the surface of the metal substrate by an enamel coating method, and calcined to form a dense and firmly bonded coating; The raw material components include: 40-55 parts of frit, 10-15 parts of clay, 6-10 parts of kaolin, 5-8 parts of borax, 5-7 parts of limestone, 6-10 parts of calcite, 6-10 parts of albite, 3-8 parts of zinc oxide and 1-2 parts of phosphorus pentoxide.

[0006] Preferably, the ball milling operation in step a is as follows: adding the ball to the ball mill in a ratio of ball: material: water = 2:3:2, first setting the speed to 300 rpm, grinding for 15 minutes, then setting the speed to 380 rpm, grinding for 15 minutes, repeating the process at this speed for 3 to 4 hours, and passing through a 200-mesh sieve to obtain a uniform ground material.

[0007] Preferably, in the step b, the ball-milled ground material is placed in a box-type resistance furnace, heated to 700° C., and kept warm for 1 hour to evaporate the water and decompose the carbonate.

[0008] Preferably, in the step d, the molten enamel is poured into water and quenched, then passed through a 20-25 mesh sieve, and then the crushed particles are placed in a drying oven and dried at 120° C. for 1-2 hours.

[0009] Preferably, the coating step in step e is to add an appropriate amount of distilled water to the glaze particles prepared in step d to obtain a porcelain slurry, and after aging for 12 hours, the metal substrate is then immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C and fired.

[0010] Further preferably, the firing is carried out in a fiber insulation furnace, the first stage is from room temperature to 200-250°C and calcined in a nitrogen atmosphere for 1-1.5 hours; the second stage is from 200-250°C to 550-600°C and calcined in a nitrogen atmosphere for 4-6 hours; the third stage is from 550-600°C to 750-800°C and calcined in a nitrogen atmosphere for 0.5-1 hour.

[0011] Compared with the existing technology, the present invention has the following technical advantages: The present invention introduces silicon dioxide through frit and clay, explores and obtains a suitable ratio, so that the viscosity of the glaze is improved, the fluidity of the glaze when it is melted is reduced, and the resistance of the glaze to water solubility and chemical erosion is increased. The coating formed by low-temperature sintering is stable and not easy to fall off during use. The glaze of the present invention strengthens the wear resistance, corrosion resistance and heat resistance, improves its protective effect, and can repair defects such as the reduction of part size caused by wear, corrosion or processing. The Ministry of Chemical Industry stipulates that the heat-resistant temperature of ordinary enamel layers is 240°C, and the heat-resistant temperature of the enamel described in the present invention is significantly improved at 385~410°C.

[0012] Silicon dioxide plays an important role in the acid resistance of porcelain glaze. The amount of silicon dioxide introduced in the present invention makes the porcelain glaze have high acid resistance and low firing temperature. The weight loss of the enamel layer of the present invention tends to be gentle as the acid and alkali corrosion time increases. The performance does not change significantly when the preparation conditions of the enamel layer are slightly changed, so the method described in the present invention has certain universality. DETAILED DESCRIPTION

[0013] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0014] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0015] In the present invention, unless otherwise specified, all "parts" and percentages (%) refer to percentages by weight.

[0016] In the present invention, unless otherwise specified, the sum of all percentages in all compositions is 100%.

[0017] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a-b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0018] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0019] In the present invention, unless otherwise specified, all the steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially; for example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially; for example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0020] In the present invention, unless otherwise specified, the specific numerical values ​​and specific substances in the embodiments of the present invention may be combined with other features of the description part of the present invention; for example, if the specification mentions that the reaction temperature is 10~100°C, and the embodiment mentions that the reaction temperature is 20°C, then it can be considered that the present invention has specifically disclosed the range of 10~20°C, or the range of 20~100°C, and this range can be combined with other features of the description part to form a new technical solution. Embodiment 1;

[0021] Weigh 41 parts of frit, 15 parts of clay, 7 parts of kaolin, 6 parts of borax, 5 parts of limestone, 6 parts of calcite, 10 parts of albite, 8 parts of zinc oxide, and 2 parts of phosphorus pentoxide, put them into a ball mill, and add them into the ball mill according to the ratio of ball: material: water = 2:3:2. First, set the speed to 300 rpm and grind for 15 minutes, then set the speed to 380 rpm and grind for 15 minutes. Repeat this speed for 4 hours, pass through a 200-mesh sieve to obtain a uniform ground material.

[0022] The ball-milled abrasive is placed in a box-type resistance furnace and heated to 700°C for 1 hour to evaporate the water and decompose the carbonate. The temperature is then raised to 1200°C for 1 hour to melt it. The molten enamel is then poured into water and crushed, then passed through a 20-mesh sieve, and the crushed particles are then placed in a drying oven and dried at 120°C for 1 hour.

[0023] An appropriate amount of distilled water is added to the prepared glaze particles to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C, and then fired in a fiber insulation furnace. The first stage is calcined from room temperature to 200-250°C in a nitrogen atmosphere for 1-1.5 hours; the second stage is calcined from 200-250°C to 550-600°C in a nitrogen atmosphere for 4-6 hours; the third stage is calcined from 550-600°C to 750-800°C in a nitrogen atmosphere for 0.5-1 hour to form a dense and firmly bonded coating. Embodiment 2:

[0024] Weigh 51 parts of frit, 10 parts of clay, 6 parts of kaolin, 5 parts of borax, 5 parts of limestone, 6 parts of calcite, 7 parts of albite, 8 parts of zinc oxide, and 2 parts of phosphorus pentoxide, put them into a ball mill, and add them into the ball mill according to the ratio of ball: material: water = 2:3:2. First, set the speed to 300 rpm and grind for 15 minutes, then set the speed to 380 rpm and grind for 15 minutes. Repeat this speed for 3.5 hours, pass through a 200-mesh sieve to obtain a uniform ground material.

[0025] The ground material after ball milling is placed in a box-type resistance furnace and heated to 700℃ for 1 hour to evaporate the water and decompose the carbonate. The temperature is then raised to 1200℃ for 0.5 hours to make it molten; the molten enamel is then poured into water for quenching and crushing, and then passed through a 20-mesh sieve, and the crushed particles are then placed in a drying oven and dried at 120℃ for 1 hour.

[0026] An appropriate amount of distilled water is added to the prepared glaze particles to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C, and then fired in a fiber insulation furnace. The first stage is calcined from room temperature to 200-250°C in a nitrogen atmosphere for 1-1.5 hours; the second stage is calcined from 200-250°C to 550-600°C in a nitrogen atmosphere for 4-6 hours; the third stage is calcined from 550-600°C to 750-800°C in a nitrogen atmosphere for 0.5-1 hour to form a dense and firmly bonded coating. Embodiment three;

[0027] Weigh 44 parts of frit, 14 parts of clay, 10 parts of kaolin, 7 parts of borax, 6 parts of limestone, 9 parts of calcite, 6 parts of albite, 3 parts of zinc oxide, and 1 part of phosphorus pentoxide, put them into a ball mill, and add them into the ball mill according to the ratio of ball: material: water = 2:3:2. First, set the speed to 300 rpm and grind for 15 minutes, then set the speed to 380 rpm and grind for 15 minutes. Repeat this speed for 4 hours, pass through a 200-mesh sieve to obtain a uniform ground material.

[0028] The ground material after ball milling is placed in a box-type resistance furnace and heated to 700℃ for 1 hour to evaporate the water and decompose the carbonate. The temperature is then raised to 1200℃ for 0.8 hours to make it molten; the molten enamel is then poured into water for quenching and crushing, and then passed through a 25-mesh sieve, and then the crushed particles are placed in a drying oven and dried at 120℃ for 1.5 hours.

[0029] An appropriate amount of distilled water is added to the prepared glaze particles to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C, and then fired in a fiber insulation furnace. The first stage is calcined from room temperature to 200-250°C in a nitrogen atmosphere for 1-1.5 hours; the second stage is calcined from 200-250°C to 550-600°C in a nitrogen atmosphere for 4-6 hours; the third stage is calcined from 550-600°C to 750-800°C in a nitrogen atmosphere for 0.5-1 hour to form a dense and firmly bonded coating. Embodiment 4:

[0030] Weigh 48 parts of frit, 12 parts of clay, 8 parts of kaolin, 6 parts of borax, 6 parts of limestone, 7 parts of calcite, 7 parts of albite, 4 parts of zinc oxide, and 2 parts of phosphorus pentoxide, put them into a ball mill, and add them into the ball mill according to the ratio of ball: material: water = 2:3:2. First, set the speed to 300 rpm and grind for 15 minutes, then set the speed to 380 rpm and grind for 15 minutes. Repeat this speed for 4 hours, pass through a 200-mesh sieve to obtain a uniform ground material.

[0031] The ball-milled abrasive is placed in a box-type resistance furnace and heated to 700°C for 1 hour to evaporate the water and decompose the carbonate. The temperature is then raised to 1200°C for 0.5 hours to melt it. The molten enamel is then poured into water and crushed, then passed through a 25-mesh sieve, and the crushed particles are then placed in a drying oven and dried at 120°C for 2 hours.

[0032] An appropriate amount of distilled water is added to the prepared glaze particles to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C, and then fired in a fiber insulation furnace. The first stage is calcined from room temperature to 200-250°C in a nitrogen atmosphere for 1-1.5 hours; the second stage is calcined from 200-250°C to 550-600°C in a nitrogen atmosphere for 4-6 hours; the third stage is calcined from 550-600°C to 750-800°C in a nitrogen atmosphere for 0.5-1 hour to form a dense and firmly bonded coating. Embodiment five;

[0033] Weigh 41 parts of frit, 15 parts of clay, 7 parts of kaolin, 6 parts of borax, 5 parts of limestone, 6 parts of calcite, 10 parts of albite, 8 parts of zinc oxide, and 2 parts of phosphorus pentoxide, put them into a ball mill, and add them into the ball mill according to the ratio of ball: material: water = 2:3:2. First, set the speed to 300 rpm and grind for 15 minutes, then set the speed to 380 rpm and grind for 15 minutes. Repeat this speed for 4 hours, pass through a 200-mesh sieve to obtain a uniform ground material.

[0034] The ground material after ball milling is placed in a box-type resistance furnace and heated to 700℃ for 1.5 hours to evaporate the water and decompose the carbonate. The temperature is then raised to 1200℃ for 1 hour to make it molten; the molten enamel is then poured into water for quenching and crushed, and then passed through a 25-mesh sieve, and the crushed particles are then placed in a drying oven and dried at 120℃ for 2 hours.

[0035] An appropriate amount of distilled water is added to the prepared glaze particles to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C, and then fired in a fiber insulation furnace. The first stage is calcined from room temperature to 200-250°C in a nitrogen atmosphere for 1-1.5 hours; the second stage is calcined from 200-250°C to 550-600°C in a nitrogen atmosphere for 4-6 hours; the third stage is calcined from 550-600°C to 750-800°C in a nitrogen atmosphere for 0.5-1 hour to form a dense and firmly bonded coating.

[0036] Performance Testing Thermal shock performance test The thermal shock resistance of the enamel layer was determined according to GB / T11419-2008 and the average value was taken after four repetitions.

[0037] Table 1 Thermal shock performance test results

[0038] The Ministry of Chemical Industry stipulates that the heat resistance temperature of ordinary enamel layer is 240℃. It can be seen from the above table that the heat resistance temperature of the enamel described in this experiment is significantly higher than that.

[0039] Corrosion resistance test The acid and alkali corrosion resistance of the enamel layer was tested according to GB4738.2-84.

[0040] Table 2 Relationship between weight loss and time of enamel layer under acid and alkali corrosion

[0041] From the above table, it can be seen that the weight loss of the enamel layer tends to be gentle as the corrosion time increases. Silicon dioxide plays an important role in the acid resistance of the enamel. The amount of silicon dioxide introduced in the present invention makes the enamel have high acid resistance and a lower firing temperature.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing low-temperature glass enamel, characterized in that: The following steps are involved: Step a: Weigh the required raw materials according to the components, put them into a ball mill, and perform intermittent ball milling; Step b: heating the ball-milled raw material to 700°C to remove moisture and impurities; Step c: Continue heating to 1200°C for 0.5 to 1 hour to make it molten; Step d: then pouring the molten enamel in step c into water, filtering, and drying the crushed particles to remove moisture; Step e: After the enamel is prepared, it is coated on the surface of the metal substrate by an enamel coating method, and calcined to form a dense and firmly bonded coating; The raw material components include: 40-55 parts of frit, 10-15 parts of clay, 6-10 parts of kaolin, 5-8 parts of borax, 5-7 parts of limestone, 6-10 parts of calcite, 6-10 parts of albite, 3-8 parts of zinc oxide and 1-2 parts of phosphorus pentoxide.

2. The method for preparing low-temperature glass enamel according to claim 1, characterized in that: The ball milling operation in step a is as follows: adding the ball to the ball mill in a ratio of ball: material: water = 2:3:2, first setting the speed to 300 rpm, grinding for 15 minutes, then setting the speed to 380 rpm, grinding for 15 minutes, repeating this speed for 3 to 4 hours, and passing through a 200-mesh sieve to obtain a uniform ground material.

3. The method for preparing low-temperature glass enamel according to claim 1, characterized in that: In the step b, the ball-milled abrasive is placed in a box-type resistance furnace, heated to 700° C., and kept warm for 1 hour to evaporate the water and decompose the carbonate.

4. The method for preparing low-temperature glass enamel according to claim 1, characterized in that: In the step d, the molten glaze is poured into water and quenched, then passed through a 20-25 mesh sieve, and then the crushed particles are placed in a drying oven and dried at 120° C. for 1-2 hours.

5. The method for preparing low-temperature glass enamel according to claim 1, characterized in that: The coating step in step e is to add an appropriate amount of distilled water to the glaze particles prepared in step d to obtain a porcelain slurry. After aging for 12 hours, the metal substrate is then immersed in the porcelain slurry for 30 seconds and then taken out, the excess glaze slurry on the surface is removed and the surface is scraped flat, and then placed in a drying oven for drying at 120°C and fired.

6. The method for preparing low-temperature glass enamel according to claim 5, characterized in that: The firing is carried out in a fiber insulation furnace. The first stage is from room temperature to 200-250°C and calcined in a nitrogen atmosphere for 1-1.5 hours; the second stage is from 200-250°C to 550-600°C and calcined in a nitrogen atmosphere for 4-6 hours; the third stage is from 550-600°C to 750-800°C and calcined in a nitrogen atmosphere for 0.5-1 hour.

Citation Information

Patent Citations

  • Enamel and preparation method thereof

    CN101921063A

  • Low-temperature light ceramic and preparation technology thereof

    CN109133855A

  • High-strength porcelain glaze and preparation method thereof

    CN110217991A

  • Domestic ceramic product with transparent glaze and preparation method thereof

    CN114773033A

  • Low-temperature glaze and glazing process thereof

    CN116444156A